The Influence Of Superstitious Beliefs And Magical Thinking On Generation Z's Purchasing Behavior In Indonesia - Heni Krisnatalia; Hendrajaya Hendrajaya; Idah Kusuma (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research is about delving into the fascinating world of Generation Z behavior, where superstition and mysterious thinking have taken on a real quality as a charming mental component. Superstitious beliefs and magical thinking, regularly formed in frivolity and common explanations, and enchanted thinking, characterized by a belief in strong causality, all influence customer choices. The aim of the research is to determine the influence of consumers' superstitious on their purchasing behavior. Furthermore, data was collected through a questionnaire in Google Forms format and a survey link was sent to consumers via the online communication media "Whats App Channels" due to time and cost limitations apart from making it easier to obtain information about generation z respondents who are willing to fill out the questionnaire. At least 30 consumers participated in the survey during the data collection process and the IBM PSPP 2.0 program was used to analyze the data obtained. As a result of the analysis, all research hypotheses were supported. Therefore, it has been determined that consumers' superstitious beliefs and magical thinking have a positive and significant influence on their purchasing behavior. Through observational investigations and case reflections, we explore the ins and outs of how superstition and fascination intersect with buyer preferences by demonstrating their beneficial value to businesses and marketers by adapting them to better suit the irrational yet effective forces at the commercial center.